Da África para o Brasil, de Orixá a Egum: as ressignificações de Exu no discurso umbandista - Nogueira, Léo Carrer (2017)
The constitution of the Exu in the Afro-Brazilian religions is the result of a long process of resignification, ruptures and hybridizations occurred in the Afro-American diaspora. In Africa, among the Yoruba peoples, Exu is a deity, an orixá, demonstrating characteristics such as communication, guide of ways, protection and sexuality. Among European and American travelers who visit this African region during the 19th and 20th centuries, Exu gains demonic characteristics, being associated with the Christian Devil. From Africa to Brazil, Exu maintains these characteristics, but also gains new interpretations: he is worshiped with many new elements in the nascent Afro-Brazilian religions. The demonization influences many members of these religions, which now incorporate it or deny it in their temples. This long process that happens throughout the twentieth century produced a new type of Eshu worshiped in temples of Brazilian Umbanda and Quimbanda. Here, Exu ceases to be considered an orixá, acquiring the status of Egum, spirit, soul of deceased person, appearing in the temples to give aid to the people. In this text we investigate the process of resignification of Exu, since he leaves Africa until reaching the Brazilians temples of Umbanda and Quimbanda, through the discourses produced about him by Umbandist intellectuals.Our central thesis is that the figure of Exu is represented in various formats in this discursive field of Umbandist literature, sometimes assuming its demonic character, others denying it and providing other explanations for its characteristics. We use Michel Foucault's discourse analysis theory to identify the continuities and ruptures of Exu in Umbanda in relation to his African ancestor.